Perilaku Pencarian Informasi Pertanian Oleh Petani Melalui Media Online - Rahmah, Siti; Adinda, Fitrah Solatia; Wardani, Ika; Purwaningtyas, Franindya (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
There are numerous communication media that can be utilized to exchange information as a result of the swift growth of technology and communication. Cybermedia, often known as online media, is one of the communication mediums that can be used. Farmers, like everyone else, require information. To get even higher yields, farmers need to know how to make compost, ward against pests, and a host of other things. According to Kuhltau, Ellis, and Wilson, the information seeking theory applied is the information seeking theory. The research methodology used in this study is library research, specifically research carried out through data collection, scientific writings that target research objects, literary data collection, or studies that are carried out to solve problems that are primarily based on a critical and in-depth analysis of the pertinent library materials. Keywords : Information Behavior, Online Media, Information, Farmers